Indonesian EFL Learners’ Willingness to Communicate in the Instructional Context - Suci Nugrah Amalia; Abdul Asib; Sri Marmanto (Indonesian Journal of EFL and Linguistics, 2019)
The principal goal of L2 education is to enhance learners’ willingness to communicate (WTC). Hence, this survey study was undertaken with the purpose of exploring Indonesian EFL learners’ WTC especially in a classroom context or the so-called Instructional WTC (IWTC) in order to know the conditions triggering their willingness and unwillingness to communicate using L2. This survey applied descriptive quantitative method where 100 EFL learners from three State Universities in Indonesia were involved as the respondents. The respondents are the English students of IAIN Curup Bengkulu, Universitas Sebelas Maret (UNS) Surakarta and Universitas Musamus Merauke Papua. Those universities represent three of five major islands in Indonesia. A questionnaire was distributed to the respondents in order to explore their WTC in six IWTC components comprising communicative self-confidence, integrative orientation, situational context of L2 use, topical enticement, learning responsibility, and off-instruction communication. The findings revealed that group size, classroom environment, students’ cohesiveness, familiarity to the topic, degree of topic preparation, classroom seating arrangement, gender, self-awareness, and familiarity with interlocutors were the factors that affected learners’ WTC. Further studies are highly recommended to deeply explore the teaching activities done by teachers by considering the influential factors of learners’ willingness and unwillingness to communicate as an effort to maximize their WTC.